Serum C - Reactive Protein Level and Peripheral Blood Picture in Children with Pneumonia - IGL Sidiartha; BNP Arhana; P Suwendra; Sudaryat S (Paediatrica Indonesiana, 1998)
This cross sectional study aimed to determine the relation between serum C-reactive protein (CRP) levels and peripheral blood picture in children with bronchopneumonia, conducted at the Division of Pulmonology, Sanglah Hospital, Denpasar during 3 months (December 1996 to February 1997). Serum CRP levels, hemoglobin, leukocyte count, neutrophil count and ESR values in 30 cases between 1 month and 4.5 years (20 male and 10 female) were measured. Bronchopneumonia was mostly found in < 1 year old (67%) and with male to female ratio of 2:1. High CRP serum level (>12 microgram/ml) was found in 33% of 30 cases. Anemia was found in 37%, leukocytosis in 50%, increase segment neutrophil ratio in 30%, increase of ESR in 40% and increase of body temperature more than 38Â°C in 4 7% of the cases. Neutrophilia, increase of ESR and increase of body temperature were found statistically significant difference between the positive CRP and negative CRP group. Most bronchopneumonia patients in this study were probably caused by non bacteria. Neutrophilia, higher ESR and higher body temperature could be used as an indicator of bacterial infection besides the increase of serum CRP levels.